A method for detecting unbond defects of absorbing coatings. (1st January 2023) - Tu, Yihang; Li, Ji; Long, Jiawei; Qin, Lin; Zhang, Yunpeng; Qiu, Yang; Ge, Meng; Zheng, Hu; Li, En
Abstract: The nondestructive test (NDT) of microwave absorbing coatings plays a very important role in radar stealth and electromagnetic compatibility. In various NDT methods, microwave thermography has shown good potential. This method uses a thermal imager to measure the surface thermal profile of absorbing coatings which are heated by microwaves. In this paper, the application of microwave thermography in defect detection of absorbing coatings is presented. Specifically, the measurement principle of microwave thermography is studied by theoretical analysis and simulation, and the influence of thermal diffusion upon defect recognition has been discussed. On this basis, an improved morphological edge detection algorithm based on dual-threshold segmentation has been proposed to get defect features. Finally, research shows that this algorithm can reduce the influence of thermal diffusion in the detection of defect geometric features.